ANALYSIS TREND OF MANPOWER PLANNING FROM INDONESIAN NAVY SOLDIER - Brillyandhi Setyarizky; Bambang Suharjo; Sunarta Sunarta (JOURNAL ASRO, 2019)
The Indonesian National Armed Forces (TNI AL), as a state institution in accordance with Law number 34 of 2004 concerning the Indonesian National Army in article 9 points stated that the Navy had a role to carry out the duties of the TNI in the development and development of sea power forces. The form of the strength of the sea dimension owned by the Navy is the Organization and the main weapon system (Alutsista), therefore the Navy has a policy in conducting organizational development and defense equipment in order to achieve the ideal strength posture, where the consequences of changes in the development of the Navy force is the need for the right number of personnel to be able to support the implementation of organizational functions and defense equipment personnel. Man Power planning includes all activities including in determining the number of troop compositions at the right time in accordance with the policies and plans of the organization and personnel of defense equipment. In the Navy organization, personnel consist of Soldiers and Civil Servants where TNI soldiers are divided into 3 groups namely Officers, Non-Commissioned Officers and Enlisted. So to deal with threats in the future, a proper planning of Soldiers is needed, therefore forecasting methods using trend analysis can be used to assist in as a basic for future planningKeywords: Manpower Planning, Forecasting, Trend Analysis.